Human MICAL1: Activation by the small GTPase Rab8 and small‐angle X‐ray scattering studies on the oligomerization state of MICAL1 and its complex with Rab8. (31st October 2018) - Esposito, Alessandro; Ventura, Valeria; Petoukhov, Maxim V.; Rai, Amrita; Svergun, Dmitri I.; Vanoni, Maria A.
Abstract: Human MICAL1 is a member of a recently discovered family of multidomain proteins that couple a FAD‐containing monooxygenase‐like domain to typical protein interaction domains. Growing evidence implicates the NADPH oxidase reaction catalyzed by the flavoprotein domain in generation of hydrogen peroxide as a second messenger in an increasing number of cell types and as a specific modulator of actin filaments stability. Several proteins of the Rab families of small GTPases are emerging as regulators of MICAL activity by binding to its C‐terminal helical domain presumably shifting the equilibrium from the free – auto‐inhibited – conformation to the active one. We here extend the characterization of the MICAL1–Rab8 interaction and show that indeed Rab8, in the active GTP‐bound state, stabilizes the active MICAL1 conformation causing a specific four‐fold increase of k cat of the NADPH oxidase reaction. Kinetic data and small‐angle X‐ray scattering (SAXS) measurements support the formation of a 1:1 complex between full‐length MICAL1 and Rab8 with an apparent dissociation constant of approximately 8 μM. This finding supports the hypothesis that Rab8 is a physiological regulator of MICAL1 activity and shows how the protein region preceding the C‐terminal Rab‐binding domain may mask one of the Rab‐binding sites detected with the isolated C‐terminal fragment. SAXS‐based modeling allowed us to propose the first model of the free full‐length MICAL1, which is consistent with an auto‐inhibited conformation in which the C‐terminal region prevents catalysis by interfering with the conformational changes that are predicted to occur during the catalytic cycle.